Effectiveness of cognitive behavioral therapy for perinatal maternal depression, anxiety and stress: A systematic review and meta-analysis of randomized controlled trials - Li, Xinyuan; Laplante, David P.; Paquin, Vincent; Lafortune, Sandra; Elgbeili, Guillaume; King, Suzanne (Clinical psychology review, 2022)
Cognitive behavioral therapy (CBT) has been widely studied in prenatal or postnatal depression, with much less research on anxiety and stress. This meta-analysis aims to comprehensively evaluate CBT efficacy for perinatal depression, anxiety and stress in the short term (from baseline to immediately post-intervention) and in the long term (from baseline to the end of follow-up). Five databases were searched. We included 79 randomized controlled trials (RCTs) and quasi-RCTs assessing the efficacy of CBT during pregnancy and the first year postpartum. Primary outcome was the mean score change in depression, anxiety and stress. CBT-only and CBT plus other interventions were effective for perinatal maternal depression in the short term (SMD −0.69, 95% CI: −0.83, −0.55) and long term (SMD −0.59, 95% CI −0.75, −0.42). CBT-only had both short- and long-term efficacy for perinatal anxiety (short term: SMD −0.63, 95% CI −0.85, −0.42; long term: SMD −0.71, 95% CI −1.02, −0.39) and short-term efficacy for perinatal stress (SMD −0.96, 95% CI −1.40, −0.52). Overall, CBT was effective for perinatal maternal depression, anxiety and stress. CBT-only exhibited short-term efficacy for perinatal depression, anxiety and stress, and long-term efficacy for perinatal depression and anxiety. Subgroup analyses suggested that CBT-only was effective across a wide variety of modalities. •Overall, CBT is effective for perinatal maternal depression, anxiety and stress.•CBT-only is effective for perinatal depression in low-income women.•Partner-inclusive CBT-only is effective for depression, anxiety and stress.•CBT-only is effective in treating and preventing depression, anxiety and stress.•CBT plus other interventions showed short- and long-term efficacy for depression.